2013
DOI: 10.1021/ie401826u
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Products Formed in the Thermal Decomposition of a Tobacco Substrate

Abstract: The identification and quantification of volatile species formed in the thermal degradation of tobacco substrates was investigated by TG-FTIR analysis. A specific experimental methodology was developed to obtain quantitative data on key components of interest present in evolved gases during TG-FTIR runs in air and nitrogen at low heating rates. Multivariate deconvolution techniques were used to identify the contributions of the key components of interest to the overall FTIR spectra. Validation runs were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 27 publications
3
29
1
1
Order By: Relevance
“…Therefore, in this work, we focus on the effect of the addition of MCM-41. The results shown in Figure 4 are in good agreement with that reported by Barontini et al [31] for the content of CO 2 , CO, water and acetaldehyde in the evolved gas from the pyrolysis of shredded tobacco. Figure 3 shows the evolution with temperature of the FTIR selected bands appearing in the spectra of the gases evolved from the thermal and catalytic pyrolysis of glycerol.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, in this work, we focus on the effect of the addition of MCM-41. The results shown in Figure 4 are in good agreement with that reported by Barontini et al [31] for the content of CO 2 , CO, water and acetaldehyde in the evolved gas from the pyrolysis of shredded tobacco. Figure 3 shows the evolution with temperature of the FTIR selected bands appearing in the spectra of the gases evolved from the thermal and catalytic pyrolysis of glycerol.…”
Section: Resultssupporting
confidence: 91%
“…In that work it was reported that the glycerol condensed in the transfer line from the TG to the FTIR spectrometer, and the signal corresponding to that compound was observed during all the experiment, as a result of the entrainment of this compound by the carrier gas throughout the experiment. Barontini et al [31] have also investigated the identification and quantification of volatile species formed in the pyrolysis of tobacco by TGA/FTIR, and developed an interesting methodology based on multivariate deconvolution techniques in order to quantify the key components of interes in smoke.…”
mentioning
confidence: 99%
“…The authors used the experimental conditions and methods similar with ones we have used for studying the electronic cigarette liquid. In the products of tobacco combustion, they have found the large amounts of carbonyl compounds of different structure [30][31][32], acetaldehyde [31], carbon monoxide [30][31][32], mixture of phenolic compounds [30,32], formic acid [30], ammonia [32], hydrogen cyanide [30] and propanal [30]. These toxic components were not detected in the presented study.…”
Section: Resultscontrasting
confidence: 60%
“…It is worth noting that there is a number of articles describing the thermal decomposition of tobacco [e. g. [30][31][32]. The authors used the experimental conditions and methods similar with ones we have used for studying the electronic cigarette liquid.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, the combustion behavior of AR materials can be divided into three regions: Region I was related to the primary degradation and evaporation of light component in AR materials (Barontini et al, 2013;Xu and Huang, 2010). As shown in Table 1, the KR material possessed a low peak temperature (T max1 ) and high weight loss in Region I.…”
Section: Tg Analysis For Ar Combustionmentioning
confidence: 99%